Case Report: Transcatheter Closure of Ruptured Sinus of Valsalva With Ventricular Septal Defect Occluder in a 3-Year-Old Child After Repair of Ventricular Septal Defect - Gong, Xueyang; Wang, Jundao; Wei, Luyao; Zhao, Tianli; Hu, Shijun (Frontiers in Pediatrics, 2021)
Sinus of Valsalva aneurysm (SVA) is a rare cardiac anomaly that can undergo spontaneous rupture into other cardiac chambers or the pericardial space. A ruptured SVA has a very poor prognosis with high morbidity and mortality. These aneurysms often present as a rupture from the right coronary sinus into the right ventricle. Transcatheter closure has become an effective alternative to surgical treatment. However, it has been rarely reported in patients after ventricular defect repair in the past. We here describe a 3-year-and-3-month-old boy who was found to have a ruptured sinus of Valsalva. He underwent surgical closure of a ventricular septal defect at the age of 2 months, which occurred in the non-coronary sinus (NCS) and ruptured into the right atrium. We successfully occluded the ruptured sinus of Valsalva with a ventricular septal occluder.